AI-Based Social Assistance for Children with Neuropsychiatric Disorders: Enhancing Social Behavior and Interaction - Natsheh, Emad; Rifaie, Masa (Journal of Science and Technology, 2025)
Children diagnoses with conditions such as ADHD or autism have difficulty with social interaction and managing emotions. These difficulties make traditional therapy inefficient. In this study, we will introduce artificial intelligence (AI) and see how it will support these children in developing better social skills. Hence, we present a tool called Spark Humanoid; an agent that uses AI to give kids feedback based on their facial expressions and how they respond during fun, and game session. The system uses convolutional neural network (CNNs) to understand the child’s emotions and applies the A* algorithm in puzzle games to offer helpful hints and adjust difficulty as needed. We tested the tool during therapy sessions with support from the Palestine Childhood Institute. The system shows promising results, since kids seemed more engaged and responded more positively when using the AI tool compared to traditional sessions. These results shows that AI could be a useful addition to therapy, giving us new ways to help children with neuropsychiatric challenges.